Management of Nephrotic Syndrome in Pediatric Patients Treated by Different Steroid Regimens - Valeria Chirico; Filippo Tripodi; Giovanni Conti; Lorena Silipigni; Antonio Lacquaniti; Paolo Monardo; Roberto Chimenz (Medicina, 2025)
Background and Objectives: The nephrotic syndrome (NS) is the most common acquired childhood kidney disease. Steroids represent the cornerstone of the therapeutic strategy, representing the first-line approach, but optimal therapeutic management is debated. This study aimed to compare different steroid therapeutic management protocols. Patients and Methods: A total of 140 NS pediatric patients were enrolled retrospectively. All the kids were divided among three different groups according to the three different steroid therapeutic schemes: 2240 mg/m2 (group 1), 3360 mg/m2 (group 2), or 3640 mg/m2 (group 3) and divided in frequently relapsing (FR-NS) or steroid-dependent (SD) NS. Results: Within group 1, 50% of the population developed FR-NS; 100% of those kids were between 2 and 6 years old. Within the second group, 54% of the patients developed FR-NS, and 83% of these kids were between 2 and 6 years old, i.e., 45% of the group population. Within group 3, 45% of the patients developed FR-NS, and 70% of these kids were among 2 and 6 years old, i.e., 32% of the group population. This group exhibits the lowest percentage (42%) of patients in the highest relapse category (≥5 relapses) compared to the other protocols, indicating that this protocol might be more effective at reducing the number of frequent relapses. No specific predictor factors of FR- or SD-NS were revealed in the studied cohort. Conclusions: A longer steroid scheme does not correlate with a better outcome, nor does it reduce the number of relapses or prevent steroid failure.